PSYCHO-EDUCATIONAL GROUP THERAPY AND SELF-COMPONENTS TRAINING ON SEXUAL ABSTINENCE AMONG IN-SCHOOL ADOLESCENTS IN ONDO STATE, NIGERIA (2016)
The consequences of early sexual debut such as sexually transmitted infections, HIV/AIDS and unintended pregnancies have brought the study of adolescent sexual behaviour to the fore of sexuality research. Attempts have been made at understanding why adolescents engage in sexual activity at an early age. However, studies on the enhancement of sexual abstinence have been under-reported in Nigeria. This study, therefore, applied Psycho-educational Group Therapy (PGT) and Self-Components Training (SCT) in encouraging sexual abstinence among in-school adolescents in Ondo State, Nigeria. It examined the moderating roles of gender and peer influence. The study was anchored on the theories of reasoned action and planned behaviour. Partial mixed design with 3x2x2 factorial matrix and qualitative approach using Focus Group Discussions (FGDs) were adopted. Multi-stage sampling technique involving stratified random sampling was used to select 121 in-school adolescents (44 males and 77 females) from three randomly selected secondary schools. The participants were screened using Sexual Abstinence Test for Adolescents and were randomly assigned into PGT, SCT and control group. Ten FGDs, which lasted three weeks, were conducted with the groups. Sexual Abstinence Scale (α = 0.89), Sexual Abstinence Test for Adolescents (α = 0.77) and Peer Pressure Inventory (α = 0.80) were used for data collection. The treatment programmes lasted eight weeks. The qualitative data were content analysed, while the null hypotheses were tested using Analysis of Covariance and Scheffe Post-hoc test at 0.05 level of significance. Participants’ age was 12.9 years ± 1.145 with 24% of them sexually debuted at a mean of 10.1 years. There was significant main effect of treatments on sexual abstinence (F(2,89) = 96.66, η2 = .710). The PGT had the highest mean score ( x =167.91) in sexual abstinence, followed by the SCT ( x =145.74) and control group ( x =127.79). However, the two way interaction of gender and peer influence was not significant. There were no significant interaction effects of treatments, gender and peer influence on sexual abstinence. Rape, curiosity, financial gain, and fear of offending the predator making the advances were major reasons for early sexual debut. Sexual abstinence improved psychological well-being and enhanced higher educational attainment. Psycho-educational Group Therapy and Self-Components Training were effective in enhancing sexual abstinence among in-school adolescents in Ondo State, Nigeria. Counselling, clinical and educational psychologists, as well as non-governmental organisations should adopt the two techniques in helping in-school adolescents. Keywords: Psycho-educational group therapy, Self-components training, Sexual abstinence, In-school adolescents in Ondo State Nigeria Word count: 402